Verdier i helse- og omsorgstjenesten. Hvordan kan reflekterende veiledning bidra til økt fokus på kommunens faglige verdigrunnlag? - Høium, Kari; Bingen, Susanne (Nordisk tidsskrift for helseforskning, 2015)
Focusing on values in health services Studies show that a focus on values in health services can encourage targeted collaboration and a proactive approach to conflict management. This study describes how a reflective value seminar can contribute to familiarizing the employees of a health care service with municipal values. An account of the different stages of the counseling seminar is made, as well as an account of methods utilized to promote knowledge of values with the contestants. The results are uplifting in regards to learning outcome from the seminar, also evident after a month of follow-up. Results indicate that newly acquired competence was deployed when meeting users and next of kin. The significance of the findings is enhanced by both the government and the research field´s emphasis, on reflection competence as a core variable in ensuring service quality. A continued challenge will be to examine appropriate models for following up the employees in order to enhance and sustain commitment and quality development in practice.